Innovative Technologies in Teaching Students of Technical Specialties: Podcasting. - Dmytro Prykhodko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2014)
Due to the fact that Ukraine is the part of the European space, important questions concerning the quality of education have arisen and thus new requirements for the teaching methods and approaches in higher technical educational institutions appear. To improve the quality of education, foreign languages teachers of technical universities are developing new teaching methods. It is very important for educators to use information technologies due to the social and educational informatization. One of the most innovative technologies in contemporary education is podcasting. The suggested paper is devoted to the analysis of podcasting as an innovative technology in the field of foreign language teaching and learning. This paper analyses the application features of the podcasting technology in the learning process. The basic concepts related to the podcasting technology (podcasting, audiocast, vodcast) are defined. The detailed process of audiocast creation is outlined. The main features of the software for audiocast creation are given. The advantages (listening sub-skills formation; listening skills development; the individualized learning intensification; creating conditions for refreshing knowledge and students' skills reinforcement in the classroom and extracurricular time; multimedia and interactivity; creativity stimulation; usability) and disadvantages (potential abstracting from studying process; audiocast selection problems) of using audiocasts in the educational process are considered.